Pengaruh Islamic Attributes dan Quality Service Terhadap Islamic Tourist Satisfaction Wisatawan Mancanegara yang Berkunjung di Kota Padang - Irda Irda; Reni Yuliviona; Elfitra Azliyanti (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This research aims to examine the effect of Islamic attributes and quality service on Islamic tourist satisfaction of foreign tourists visiting the city of Padang. The research was conducted on 100 foreign tourist with a purposive sampling technique. The data analysis technique in this through two general stages, namely the measurement model and structural model, these two stages will be analyzed by using PLS 2.0M3 software. The results of the research show that Islamic attributes and quality service have a positive and significant effect on the Islamic tourist satisfaction of foreign tourist visiting the city of Padang.